2018
DOI: 10.1080/23744235.2018.1441538
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Hybrid Capture 2 to Cobas 4800 in Hpv detection: sensitivity and specificity for Cin2+ in two time periods

Abstract: The detection rate of CIN2+ was higher in the first period than in the second period. There was no significant difference in sensitivity of HC2 and Cobas 4800 in women with CIN2+. The specificity of CIN2+ using Cobas 4800 in the second period was higher than HC2 in the first period, probably due to the lower prevalence of CIN2+ in the second period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The results showed that the coincidence rate of the Cobas HPV test and HC2 test was 90% in the primary screening for cervical cancer. Similar results were performed in the researches of other scholars using Cobas HPV and HC2 test [15, 16]. In addition, the Cobas HPV positive rate and HPV16/18 typing positive rate had a U-shaped distribution with age were presented in our study, and there were two peak age groups, 20–29 years old and 60+ years old.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that the coincidence rate of the Cobas HPV test and HC2 test was 90% in the primary screening for cervical cancer. Similar results were performed in the researches of other scholars using Cobas HPV and HC2 test [15, 16]. In addition, the Cobas HPV positive rate and HPV16/18 typing positive rate had a U-shaped distribution with age were presented in our study, and there were two peak age groups, 20–29 years old and 60+ years old.…”
Section: Discussionsupporting
confidence: 90%
“…The cobas ® 4800 assay has been approved by the US-FDA for use as a stand-alone assay for the screening of cervical cancer [41]. The cobas ® 4800 assay has been clinically evaluated and has significant sensitivity for the detection of CIN2+ lesions [20,21,42]. Moreover, all steps of the cobas ® 4800 assay could be completed on a fully automated machine.…”
Section: Discussionmentioning
confidence: 99%
“…Although various HPV-DNA detection tests exist, the five US Food and Drug Administration (US FDA)-approved assays detect only the HR-HPV types [18,19]. It has been reported that HR-HPVs testing showed a significant sensitivity for detecting CIN2+ lesions [20][21][22]. Some national cervical cancer screening programs rely solely on HPV primary testing [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation